2021
DOI: 10.51372/bioagro332.8
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota edáfica en lotes de plátano con vigor contrastante y su relación con propiedades del suelo

Abstract: Los organismos edáficos son responsables en la regulación de procesos biológicos, como la mineralización y la reparación biológica del suelo. Con el propósito de cuantificar la microbiota del suelo cultivado con plátano cv Hartón en el Sur del Lago de Maracaibo, se seleccionaron siete unidades de producción con lotes de plantas de alto y bajo vigor (AV y BV). En cada parcela se seleccionaron 20 plantas a las que se determinó el número de manos por racimo, circunferencia de la planta madre y altura del hijo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…Higher water retention and higher content of organic matter promote better conditions for the development and activity of soil microorganisms. Results of the effect of these edaphic properties on microorganisms have been reported by Olivares et al [9] and González-García et al [13]. The results of Millán et al [47] showed that the FLN genera found are sensitive to slight changes in soil pH, and show dependence on the porosity and soil moisture.…”
Section: Debiased Sparse Partial Correlation Algorithm (Dspc)mentioning
confidence: 68%
See 3 more Smart Citations
“…Higher water retention and higher content of organic matter promote better conditions for the development and activity of soil microorganisms. Results of the effect of these edaphic properties on microorganisms have been reported by Olivares et al [9] and González-García et al [13]. The results of Millán et al [47] showed that the FLN genera found are sensitive to slight changes in soil pH, and show dependence on the porosity and soil moisture.…”
Section: Debiased Sparse Partial Correlation Algorithm (Dspc)mentioning
confidence: 68%
“…The high microbial activity was closely related to the soil texture, and, in turn, this positively influenced the biometric parameters of the plants. The study by González-García et al [13] and Rondón et al [16] shows that the bulk density, content of fine particles, organic matter, and carbon and microbial coefficient, were favorable for the high productivity batches. In general, there were no statistical differences in fungal and bacterial colony-forming units (CFU) between vigor batches.…”
Section: Debiased Sparse Partial Correlation Algorithm (Dspc)mentioning
confidence: 95%
See 2 more Smart Citations
“…Las prácticas agrícolas convencionales, como la labranza intensiva en combinación con la incineración de restos vegetales, han exacerbado la degradación del suelo (Cortes & Acevedo, 2019;Latorre & Villamizar, 2019;Buelvas, 2021;2022;Flores et al, 2021). Al mismo tiempo recientes investigaciones demuestran, que los animales de pastoreo alteran sustancialmente las propiedades fisicoquímicas del suelo, provocando erosión, compactación y reducción del espacio poroso, influyendo a su vez en la velocidad del flujo de agua y modificando el equilibrio de los nutrientes; además, de reducir el contenido de materia orgánica, pérdida de la diversidad y disminución de la fertilidad (González-Pedraza & Dezzeo, 2011;2014a;Villanueva et al, 2014).…”
Section: Introductionunclassified